Restoring the night - Cieszykowski, Jeannette Marie (Kansas State University, 2014)
Restorative landscapes, healing gardens, and therapeutic gardens can improve mental and physical health. They relieve stress, slow us down and make us appreciate the present moment (Kaplan 1995). Research confirms these benefits: “A restorative environment provides measurable physical and/or psychological benefit to human health” (Krinke 2005, 107). Unfortunately, few restorative landscapes are designed for night time use, though stress and the need for healing occur at all hours of the day and night. To that end, the purpose of this research is to create a set of lighting design strategies that will enable designers to create restorative landscapes for nighttime use and demonstrate how they can be applied. A literature review synthesizing the information on healing garden types, outdoor lighting techniques, and their relationship to Attention Restoration Theory, identified four main components required for a space to be considered restorative. Two precedent studies allowed the author to explore the components of Attention Restoration Theory and healing garden types. The lighting principles that afford these four components and healing garden types that are best suited for an urban public space were layered in a final design to create a restorative urban space that is functional at night. The set of design strategies created with the support of this research was applied to Occidental Square, a public park in Seattle, Washington. The applied design strategies are represented and demonstrated through the site design. With these tools in hand, designers can create spaces for those in need of rejuvenation, restoration, and tranquility not only during the day, but also at night.
Keywords: Attention restoration theory; Restorative landscapes; Lighting; Landscape lighting; Healing landscapes; Night; Architecture (0729); Landscape Architecture (0390)